Identification of volatile markers for the detection of adulterants in red ginseng (Panax ginseng) juice using headspace stir‐bar sorptive extraction coupled with gas chromatography and mass spectrometry. Issue 14 (4th July 2018) - Lee, Jangho; Shibamoto, Takayuki; Ha, Jaeho; Jang, Hae Won
Abstract: Red ginseng ( Panax ginseng ) products are frequently adulterated by manufacturers with cheaper medicinal plant products including deodeok ( Codonopsis lanceolata ) and doraji ( Platycodon grandiflorum ) to increase profits. To identify possible volatile markers for the adulteration of red ginseng juices with deodeok or doraji, a headspace stir‐bar sorptive extraction method was developed. Gas chromatography with mass spectrometry and untargeted metabolomics analysis revealed that 1‐hexanol, cis‐ 3‐hexen‐1‐ol, and trans ‐2‐hexen‐1‐ol are abundantly present in deodeok and doraji but not red ginseng. The peak area ratios in gas chromatograms of these compounds in red ginseng juices mixed with deodeok or doraji indicate that these volatile chemicals can be used as markers to detect the adulteration of red ginseng juice.